A Study on Emerging Human Resource Practices at Call Centers in Coimbatore City - Latha, M. (Gyan Management Journal, 2009)
The human resources function has become a. key driver of organi,zalional performance, as talent has emerged as the most critical element in business success. The l!R executive stands al the intersection of strategy and
Keywords: information technology; ITES- information teclmoLogy enabLetL services; ACD - automatic call dislribution; HRM - human resource management; Inbound call - calls coming in (call center) from outside; Outbound call - calls going out (customer) from call center